Programa de Intervención como Neuroprotector en los Adultos Mayores (2023)
The growth of the older adult population is progressively increasing, with them cognitive impairment is becoming more and more present in the population. Therefore, it is of great importance to intervene the affected cognitive processes with a stimulation method that presents neuroprotectors.